Liderazgo y administración de empresas contemporáneas (2020)
The purpose of this research is to demonstrate the importance of leadership in contemporary administration and how it is involved in the Management of Human Talent. Leadership and administration will be studied chronologically from its beginnings in the nineteenth century to the current date and the approaches that each of these has, as mentioned above, it would be defined which is the theory of leadership that best suits contemporary administration. It will also be mentioned because leadership is important in organizations and how this from the area of Human Talent influences the objectives proposed.